Sartorial politics in early modern Europe : fashioning women - Griffey, Erin (Amsterdam : Amsterdam University Press, 2019)
For women at the early modern courts, clothing and jewelry were essential elements in their political arsenal, enabling them to signal their dynastic value, to promote loyalty to their marital court and to advance political agendas. This is the first collection of essays to examine how elite women in early modern Europe marshalled clothing and jewelry for political ends. With essays encompassing women who traversed courts in Denmark, Finland, England, France, Germany, Habsburg Austria, Poland-Lithuania, Italy, Spain and Portugal, the contributions cover a broad range of elite women from different courts and religious backgrounds as well as varying noble ranks
Introduction / Erin Griffey -- 1. Isabella d'Este's sartorial politics / Sarah Cockram -- 2. Dressing the queen at the French Renaissance court : sartorial politics / Isabelle Paresys -- 3. Dressing the bride : weddings and fashion practices at German princely courts in the fifteenth and sixteenth centuries / Kirsten O. Frieling -- 4. Lustrous virtue : Eleanor of Austria's jewels and gems as composite cultural identityand affective maternal agency / Lisa Mansfield -- 5. Queen Elizabeth : studded with costly jewels / Susan Vincent -- 6. A "Cipher of A and C set on the one Syde with diamonds" : Anna of Denmark's jewellery and the politics of dynastic display / Jemma Field -- 7. "She bears a duke's revenues on her back" : fashioning Shakespeare's women at court / Robert I. Lublin -- 8. How to dress a female king : manifestationsof gender and power in the wardrobe of Christina of Sweden / Julia Holm -- 9. Clothes make the queen : Mariana of Austria's style of dress, from archduchess to queen consort (1634-1665) / Laura Olivan Santaliestra -- 10. "The best of Queens, the most obedient wife" : fashioning a place for Catherine of Braganza as consort to Charles II / Maria Hayward -- 11. Chintz, china, and chocolate : the politics of fashion at Charles II's court / Juliet Claxton, Evelyn Welch -- 12. Henrietta Maria and the politics of widows' dress at the Stuart court / Erin Griffey.
Includes bibliographical references (pages 303-332) and index
Print version record.
JSTOR
Keywords: Women's clothing -- Europe -- History -- 16th century; Women's clothing -- Europe -- History -- 17th century; Women's clothing -- Political aspects -- Europe -- History -- 16th century; Women's clothing -- Political aspects -- Europe -- History -- 17th century; Jewelry -- Political aspects -- Europe -- History -- 16th century; Jewelry -- Political aspects -- Europe -- History -- 17th century; Nobility -- Clothing -- Europe -- History -- 16th century; Nobility -- Clothing -- Europe -- History -- 17th century; Vêtements de femme -- Europe -- Histoire -- 16e siècle.; Vêtements de femme -- Europe -- Histoire -- 17e siècle.; Vêtements de femme -- Aspect politique -- Europe -- Histoire -- 16e siècle.; Vêtements de femme -- Aspect politique -- Europe -- Histoire -- 17e siècle.; Bijoux -- Aspect politique -- Europe -- Histoire -- 16e siècle.; Bijoux -- Aspect politique -- Europe -- Histoire -- 17e siècle.; ART / History / Renaissance; Nobility -- Clothing; Women's clothing; Europe; Frau; Hof; Kleidung; Politik; Schmuck; Europa; 1500-1699; Electronic books; History